Wages, Flexible Exchange Rates, and Macroeconomic Policy - Sachs, Jeffrey (Quarterly Journal of Economics, 1980)
In an open economy with a floating exchange rate, the efficacy of fiscal and monetary policy depends fundamentally on the wage-setting process. In the canonical models of Mundell and Fleming, monetary expansion raises output via an exchange rate depreciation, while fiscal expansion has no output effect. These results hold only when real wages can be altered by exchange rate movements; if the real wage is fixed, the Mundell-Fleming ranking of policy is reversed. This paper explores the interaction of wages and policy in short- and long-run models, under the assumptions of perfect foresight and world capital mobility.